MORTALIDADE MATERNA: ANÁLISE EPIDEMIOLOGICA NACIONAL E DE UM ESTADO DO BRASIL CENTRAL - Karine Cavalcante da Costa (2025)
Maternal mortality is one of the main indicators for evaluating a health system around the world, as it is related to multifactorial causes. For this reason it was considered one of the Sustainable Development Goals (SDG). This analytical research, of a quantitative nature, aims to analyze the national epidemiological situation of maternal mortality in Brazil and Mato Grosso do Sul. To this end, a scoping review was carried out in order to identify the main causes/risk factors for this indicator in the country and analyze its epidemiological situation in Brazil, the State of Mato Grosso do Sul and health macro-regions in 2022, with data obtained by the Brazilian Obstetric Observatory. It was observed that the causes/risk factors remained the same for four decades, according to the period surveyed in the literature found, with social causes being: age, education, race/color, income and marital status. Among the causes related to the service are: the low quality of prenatal care and health records and cesarean section as the main ones. Gestational hypertensive diseases, followed by hemorrhage and abortion were the direct causes, while cardiovascular diseases were indirect causes. These causes can be observed in the epidemiological analysis in the period of 2022 and that, despite the HDI considered high for the national level and for the state, the indicators still have a negative impact on maternal mortality, with emphasis on the macro-region of Corumbá, which demonstrated the worst indicators of the regions studied. It was concluded that there is a need for intersectoral strategies and qualification of specific health services, according to regional characteristics, so that they can impact the reduction of this problem. Descriptors: maternal mortality; causality; risk factors; determinants; evaluation of health services.